Method for producing carbamate-esterified cellulose fibers

By introducing a heating reaction in the papermaking process of cellulose fibers, the reaction between urea and cellulose fibers is used to achieve carbamate, which solves the problem that cellulose fiber modification in the prior art is not suitable for mass production, and achieves efficient production of carbamate cellulose fibers.

CN119522239APending Publication Date: 2025-02-25DAIO PAPER CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380052177.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-03-01
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the modification effect of cellulose fibers when mass production of carbamate cellulose fibers, especially when the cellulose fibers are restricted in the state of aqueous dispersion in advance.

Method used

Papermaking technology is used to manufacture pulp sheets, and the urea in the pulp sheets reacts with cellulose fibers through heating to achieve carbamate. The method includes performing heat treatment on the pulp sheet passing between the rollers, dividing it into a drying part and a reaction part using a plurality of consecutive sets of rollers, and controlling the temperature and passing time of each portion to achieve sufficient modification.

Benefits of technology

It realizes efficient modification in mass production of carbamate cellulose fibers, improves the dispersion of cellulose fibers and the enhancement effect of resins, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522239A_ABST
    Figure CN119522239A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a method for producing a urethane-esterified cellulose fiber that can be mass-produced. [Solution] A method for producing carbamate cellulose fibers, which is characterized in that, when producing carbamate cellulose fibers, a pulp sheet containing urea is passed between two or more consecutive pairs of rollers at a speed of 300 m / min to 3000 m / min, heated and modified by the heating, and the number of the consecutive pairs of rollers is at least two, and the number of the consecutive pairs of rollers is at least two. The present invention is characterized in that one or more sets of preceding sets are used as drying units, one or more sets of succeeding sets are used as reaction units, the temperature of rollers belonging to the drying units is 80-130 DEG C, the temperature of rollers belonging to the reaction units is 220 DEG C or more, and the number of pairs of rollers is set so that the passage time of the drying units is 8 seconds or more, and the passage time of the reaction units is 8 seconds or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing carbamate-treated cellulose fibers. Background Art

[0002] Microfibers such as cellulose nanofibers and microfibril cellulose (microfibrillated cellulose) have long attracted attention, and in recent years, proposals have been made to introduce anionic groups into cellulose fibers (modify them with anionic groups) and the like (see Patent Document 1).

[0003] In addition, the use of fine fibers as a reinforcing material for resins has attracted much attention. Since fine fibers are hydrophilic and resins are hydrophobic, a scheme for replacing the hydroxyl groups of fine fibers with carbamate groups has been proposed (see Patent Document 2). According to this scheme, the dispersibility of the fine fibers is improved, thereby improving the reinforcing effect of the resin.

[0004] However, in the above scheme, when modifying the cellulose fibers, the cellulose fibers need to be in a state of aqueous dispersion in advance, which is not suitable for mass production.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2021-75665

[0008] Patent Document 2: Japanese Patent Application Publication No. 2019-1876 Summary of the invention

[0009] Problems to be solved by the invention

[0010] An object of the present invention is to provide a method for producing urethanized cellulose fibers that can be mass-produced.

[0011] Means for solving problems

[0012] First, the inventors of the present invention thought whether the technology for producing pulp sheets in the field of papermaking technology could be used when mass-producing urethanized cellulose fibers. However, in the field of papermaking technology, the pulp sheet itself is the target product, whereas in the present invention, the pulp sheet is only temporarily used in its form or shape. Therefore, from the perspective of rapid urethanization, the papermaking technology could not be directly used. Therefore, after repeated experiments, and focusing on urethanization in particular, the following means were thought of.

[0013] That is, a method for producing carbamate-modified cellulose fibers, characterized in that, when producing carbamate-modified cellulose fibers in which a part or all of the hydroxyl groups of cellulose fibers are modified with carbamate groups,

[0014] A pulp sheet containing at least one of urea and a urea derivative, which is made into a strip by making a raw material pulp into paper, is passed between a pair of rolls at a speed of 300 m / min to 3000 m / min and heated, and the modification is performed by the heating.

[0015] The above-mentioned roller pairs are set as two or more sets of continuous roller pairs.

[0016] The first group or two or more groups are used as the drying part, and the second group or two or more groups are used as the reaction part.

[0017] The temperature of the rollers in the drying section is set to 80° C. to 130° C., and the temperature of the rollers in the reaction section is set to 220° C. or higher.

[0018] The number of sets of the pair of rolls is set to a number such that the passage time of the drying section is 8 seconds or longer and the passage time of the reaction section is 8 seconds or longer.

[0019] Effects of the Invention

[0020] According to the present invention, there is provided a method for producing urethanized cellulose fibers which can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is an explanatory diagram of the steps of obtaining urethanized fine fibers from raw material pulp. DETAILED DESCRIPTION

[0022] Next, a specific embodiment will be described. It should be noted that this embodiment is an example of the present invention, and the scope of the present invention is not limited to the scope of this embodiment.

[0023] like Figure 1 As shown, the manufacturing method of this embodiment can be mainly divided into: a step X1 to obtain a cellulose fiber-containing material P2 that can be used as a "pulp sheet containing at least any one of urea and urea derivatives (also referred to as "urea, etc.")" from a raw pulp P1; a step X2 to obtain carbamate-treated cellulose fibers P3 by reacting urea, etc. after the step X1; and a step X3 to obtain carbamate-treated fine fibers P4 by opening the carbamate-treated cellulose fibers P3 after the step X2.

[0024] The step X1 to obtain the cellulose fiber-containing material P2 can be mainly divided into a papermaking step 100 of making a strip-shaped pulp sheet from the raw material pulp P1 and a coating step 200 of coating the pulp sheet with urea or the like. These steps will be described below in order.

[0025] (Raw pulp)

[0026] As the raw material pulp P1, for example, one or more kinds can be selected from wood pulp made from broad-leaved trees, coniferous trees, etc., non-wood pulp made from straw, bagasse, cotton, hemp, bast fiber, etc., and waste paper pulp (DIP) made from recycled waste paper, broken paper, etc.

[0027] In order to avoid the mixing of impurities as much as possible, wood pulp is preferably used as the raw material pulp P1. As the wood pulp, for example, one or more kinds of chemical pulps such as broadleaf kraft pulp (LKP) and coniferous kraft pulp (NKP), mechanical pulp (TMP), etc. can be selected and used.

[0028] The hardwood kraft pulp may be hardwood bleached kraft pulp, hardwood unbleached kraft pulp, or hardwood semi-bleached kraft pulp. Similarly, the conifer kraft pulp may be conifer bleached kraft pulp, conifer unbleached kraft pulp, or conifer semi-bleached kraft pulp.

[0029] Among them, it is preferred to use NKP (preferably NBKP) and LKP (preferably LBKP) together. In this regard, the cellulose fibers of NKP are thick and long, so the strength of the cellulose fiber content is improved, but the texture is deteriorated. On the other hand, the cellulose fibers of LKP are thin and short, so the strength of the pulp sheet is reduced during papermaking, but the texture is improved. Based on such characteristics, when NKP and LKP are used together, the mixing ratio of NKP is preferably 1 to 99% by mass, more preferably 5 to 95% by mass, and particularly preferably 10 to 90% by mass. If the mixing ratio of NKP is less than 10% by mass, paper breaks may occur in the papermaking process and the coating process due to insufficient tensile strength and tear strength. On the other hand, if the mixing ratio of NKP exceeds 90% by mass, that is, if the mixing ratio of LKP is less than 10% by mass, it may not be possible to fully obtain characteristics such as the reinforcing effect of the resin.

[0030] On the other hand, as mechanical pulp, for example, one or more kinds can be selected from stone ground pulp (SGP), pressure stone ground pulp (PGW), wood ground pulp (RGP), chemical fine grinding pulp (CGP), thermogrind pulp (TGP), grinding pulp (GP), thermomechanical pulp (TMP), chemical thermomechanical pulp (CTMP), disc mechanical pulp (RMP), bleached thermomechanical pulp (BTMP) and the like.

[0031] The freeness of the raw pulp P1 measured in accordance with JIS P 8121-2 is preferably 200 to 700 cc, more preferably 250 to 650 cc, and particularly preferably 300 to 600 cc. If the freeness is less than 200 cc, dehydration in the wire section described later is poor, and the papermaking speed may not be increased. On the other hand, if the freeness exceeds 700 cc, the texture is poor, and the paper may break in the subsequent coating step.

[0032] In the raw pulp P1, it is preferred to add a sizing agent internally and / or externally as needed to adjust the Stokes sizing degree (JIS P 8122) and the Cobb sizing degree (JIS P 8140). In this regard, the Stockigt sizing degree is a test for measuring the time required for a reagent to penetrate into a pulp sheet and develop color, and the lower the value, the higher the permeability. On the other hand, the Cobb sizing degree is a test for measuring the amount of water (mass) absorbed when one side of a pulp sheet is in contact with water for a certain period of time, and the higher the value, the higher the water absorption. Therefore, the Stockigt sizing degree as an indicator of permeability and the Cobb sizing degree as an indicator of water absorption are greatly different in the case where a sizing agent is included and the case where a sizing agent is not included. However, if the amount of the sizing agent is large, the amount of urea or the like added (penetration amount) in the coating step described later is insufficient, and the reaction may become insufficient. On the other hand, if the amount of the sizing agent is small, paper breakage may occur due to reduced wet paper strength. Therefore, the amount of the sizing agent added needs to be adjusted, and this amount can be based on the Stockigt sizing degree or the Cobb sizing degree of the pulp sheet before coating with urea or the like.

[0033] Specifically, the Stockigt sizing degree measured in accordance with JIS P 8122 is preferably 0.1 to 100 seconds, more preferably 0.2 to 80 seconds, and particularly preferably 0.5 to 50 seconds. In addition, the Cobb sizing degree (10 seconds) measured in accordance with JIS P 8140 is preferably 10 to 600 g / m 2 , more preferably 20 to 580 g / m 2 , particularly preferably 30 to 550 g / m 2 .

[0034] The ash content of the raw material pulp P1 measured in accordance with JIS P 8251 is preferably 0 to 20 mass %, more preferably 0 to 15 mass %, and particularly preferably 0 to 10 mass %. If the ash content exceeds 20 mass %, the strength of the wet pulp sheet decreases, and paper breakage may occur particularly in the coating step.

[0035] It should be noted that the manufacturing method of this embodiment is not a method for manufacturing paper, but only utilizes the state or form of a pulp sheet in order to efficiently react urea, etc. Therefore, the knowledge related to ash addition in paper manufacturing technology cannot be directly utilized. For example, when fiber opening is performed in a subsequent process, the amount of ash also affects the fiber opening process.

[0036] (Papermaking process)

[0037] In the manufacturing method of this embodiment, raw material pulp P1 is paper-made to form a strip-shaped pulp sheet in the papermaking step 100. Here, the strip-shaped refers to a continuous elongated sheet having a predetermined width (e.g., 300 mm to 10,000 mm), and refers to a shape that is the same or similar to wet paper or paper web in the paper manufacturing process.

[0038] Examples of papermaking equipment used in the papermaking step 100 include a Fourdrinier former having a wire section 110, a press section 120, etc., a former in which an on top former is combined with a Fourdrinier former, and a gap former.

[0039] Among them, the use of a gap former in which the stock jet ejected from the headbox is immediately sandwiched between two wires has the advantage that the difference between the front and back is small and urea etc. can be uniformly infiltrated into the pulp sheet in the thickness direction (Z-axis direction) of the pulp sheet.

[0040] However, although the sandwich former has the advantage of small difference between the front and the back, it has poor flatness because both sides are mesh surfaces. In addition, the texture is determined at the moment when the paper material is blown onto the mesh, so it has the characteristics of poor texture. In this method, since the production of paper itself is not the purpose, flatness and texture may not be a problem, but from the perspective of the relationship with the coating method in the later stage and the relationship with the permeability of the reagent, it is preferred to use a fourdrinier with an on top former because the flatness and texture are excellent. In particular, if a shaking device (a device that shakes the mesh horizontally) is installed on the mesh, the texture is further improved, which is preferred.

[0041] The pulp sheet (paper layer) of the wire section 110 flows to (is transferred to) the press section 120 and is dehydrated.

[0042] The press used in the press section 120 may be, for example, a straight type, an inverted type, a reverse type, or a combination thereof. Of these, the straight type without open traction is preferred because it is easy to hold the pulp sheet and has fewer operational problems such as paper breaks.

[0043] The pulp sheet (wet paper) that has passed through the press section 120 can be transferred to a single-layer or double-layer pre-drying section 130 for drying. The pre-drying section 130 is preferably a single-layer dryer of a non-open traction type, because it reduces paper breakage and can be dried efficiently without reducing the volume.

[0044] The drying temperature in the pre-drying section 130 is preferably 80 to 140° C., more preferably 85 to 135° C., and particularly preferably 90 to 130° C. If the drying temperature exceeds 140° C., partial overdrying occurs, and the penetration of urea or the like in the coating step 200 may be poor in the overdried portion. On the other hand, if the drying temperature is lower than 80° C., partial poor drying occurs, and paper breakage may occur in the poorly dried portion.

[0045] The moisture content of the pulp sheet after the pre-drying section 130 is preferably 0.1 to 10%, more preferably 1 to 9%, and particularly preferably 2 to 8%. If the moisture content is less than 0.1%, the pulp sheet is too dry and the penetration of urea or the like in the coating step 200 may be poor. On the other hand, if the moisture content exceeds 10%, the pulp sheet is poorly dried and paper breakage may occur in the coating step 200.

[0046] In this form, the said water content is the value measured by infrared ray using a BM meter (basis weight / water content).

[0047] The tape-shaped pulp sheet obtained in the papermaking step 100 preferably has a basis weight of 60 to 800 g / m2 as measured in accordance with JIS P 8124. 2 , more preferably 80 to 750 g / m 2 , particularly preferably 100 to 700 g / m 2 If the basis weight is less than 50g / m 2 If the basis weight exceeds 800 g / m 2 urea etc. may not be able to fully penetrate in the coating step 200. It should be noted that the above basis weight is for a single-layer papermaking. If a multi-layer papermaking is performed with two or more layers, the reagent may remain at the interface of the layer.

[0048] Urea or the like applied in the coating step 200 may contain any papermaking reagent. There is no limitation on the type of papermaking reagent, and the concentration of the papermaking reagent may be appropriately adjusted as needed. However, it is necessary not to damage the purpose of applying urea or the like, and sometimes it is necessary to make adjustments. For example, in the present embodiment in which urea or the like is used in the coating step 200, in the papermaking step 100, papermaking is performed in such a manner that the concentration of papermaking reagents such as various starches, CMC (carboxymethyl cellulose) having a hydroxyl group, colloidal silica, aluminum sulfate, etc. having a silanol group or the like bonded to a certain element with -OH groups, rosin sizing agents, ASA (alkenyl succinic anhydride), AKD (alkyl ketene dimer), various starches, CMC, etc. is preferably 0 to 10%, more preferably 0.1 to 9%, and particularly preferably 0.2 to 8%. Since the above papermaking reagents are subjected to modification reactions caused by urea or the like, if the above papermaking reagents are contained in large amounts, the use of urea or the like in the reaction step X2 will be hindered accordingly. The above reagents do not depend on internal or external addition.

[0049] On the other hand, the dye is determined according to the subsequent use. For example, when the use is a resin reinforcement material and coloring of fine fibers is not preferred, papermaking is performed with the dye preferably at 0 to 10%, more preferably 0.1 to 5%, and particularly preferably 0.2 to 3%.

[0050] From the same viewpoint, the pulp sheet preferably has a whiteness of 80% or more, more preferably 82% or more, and particularly preferably 85% or more as measured in accordance with JIS P 8148. When LBKP and NBKP are used as the raw material pulp P1 as in the above example, the whiteness is usually 80% or more, and there is no need to adjust the whiteness.

[0051] The tensile strength of the pulp sheet measured in accordance with JIS P 8113 is preferably 10 MPa or more, more preferably 15 MPa or more, and particularly preferably 20 MPa or more. When the tensile strength is less than 10 MPa (1 kN / m, thickness 100 μm), paper breakage may occur in the coating step 200. However, although the tensile strength increases when the basis weight is increased, as described above, if the basis weight is increased, urea and the like are difficult to penetrate in the coating step 200. Therefore, the balance between the tensile strength and the basis weight is also important, and the specific tensile strength (tensile strength / basis weight) is preferably 1 to 10000 Nm / g, more preferably 5 to 5000 Nm / g, and particularly preferably 10 to 1000 Nm / g.

[0052] On the other hand, the wet paper strength of the pulp sheet measured in accordance with JIS P 8135 is preferably 0.1 kN / m or more, more preferably 0.2 kN / m or more, and particularly preferably 0.5 kN / m or more. When the wet paper strength is less than 0.1 kN / m, paper breakage may occur in the coating step 200. However, although the wet paper strength is increased when the basis weight is increased, as described above, it is difficult for urea and the like to penetrate in the coating step 200 when the basis weight is increased. Therefore, the balance between the wet paper strength and the basis weight is also important, and the specific wet paper strength (wet paper strength / basis weight) is preferably 0.1 to 5000 Nm / g, more preferably 0.5 to 1000 Nm / g, and particularly preferably 1 to 500 Nm / g.

[0053] (Coating process)

[0054] The pulp sheet dried in the pre-drying section 130 is coated with urea or the like in the coating section 210 between the pre-drying section 220 and the post-drying section 220. Here, in this specification, "coating" only refers to the "coating" behavior, and is not intended to limit the state of the urea or the like after coating. Therefore, for example, in addition to the mode in which the urea or the like remains on the surface of the pulp sheet to form a coating layer, the mode in which the urea or the like completely penetrates into the pulp sheet and does not form a coating layer on the surface of the pulp sheet, that is, the mode in which the urea or the like is only in the impregnation state, is also included.

[0055] In the coating section 210, urea or the like can be coated by coating methods such as bevel blade coating, size press coating, tough blade coating, rod coating, impregnation coating, spray coating, and comma blade coating. Among them, the coating in the coating section 210 is preferably performed by tough blade coating. In this regard, tough blade coating is a type of blade coating, and in bevel blade coating, which is also a type of blade coating, urea or the like sprayed from an injector is scraped off, while in tough blade coating, urea or the like is pressed into the pulp sheet while coating. Therefore, this method is suitable for the present method in which it is highly necessary to make urea or the like penetrate into the pulp sheet.

[0056] On the other hand, the impregnation coating and the comma blade coating each have the following characteristics.

[0057] That is, first, in this method, the impregnation method refers to a method of coating by moving the pulp sheet in a container filled with urea, etc. In addition, the comma blade coating refers to a method of coating by forming a liquid pool between two rollers and a blade and moving the pulp sheet between the gaps to adjust the coating amount.

[0058] The concentration of urea or the like can be appropriately adjusted as needed. In the present embodiment of carbamate formation, it is preferably 20 to 50% by mass, more preferably 25 to 45% by mass, and particularly preferably 30 to 40% by mass. If the concentration of urea or the like is less than 20% by mass, the carbamate formation rate is insufficient and drying may be difficult. On the other hand, if the concentration of urea or the like exceeds 50% by mass, when urea water is prepared, the temperature of the solution decreases due to the endothermic reaction caused by the dissolution of urea or the like, and urea or the like may precipitate.

[0059] The viscosity of urea water (40% concentration) measured in accordance with JIS-Z8803 (2011) is preferably 2000 cps or less, more preferably 1700 cps or less, and particularly preferably 1500 cps or less. If the viscosity exceeds 2000 cps, urea water will have difficulty penetrating into the pulp sheet.

[0060] In the production method of this embodiment, the coating step 200 can be performed offline or online. However, when the production speed is 300 m / min or more, it is preferred to sequentially introduce the papermaking step 100 and the coating step 200 as continuous processes in the machine (online). If the on-line method is adopted, the production efficiency is improved, and the coating can be uniformly applied without being affected by the storage state of the pulp sheet.

[0061] In the production method of this embodiment, urea or the like may be applied to only one side of the pulp sheet or to both sides, but it is preferred to apply it to both sides from the viewpoint of uniformity of the reaction performed in the subsequent step.

[0062] In addition, when urea or the like is applied to both sides of a pulp sheet in an off-line manner, there is an advantage that the coating amount can be made different on the front and back sides according to the characteristics of the pulp sheet.

[0063] The coating mass ratio of urea, etc. to cellulose fibers (urea, etc. / cellulose fibers) is preferably 10 to 400 kg / pt (pulp ton), more preferably 20 to 300 kg / pt, and particularly preferably 45 to 200 kg / pt. If the coating mass ratio is less than 45 kg / pt, urethane formation may not proceed sufficiently. On the other hand, if the coating mass ratio exceeds 200 kg / pt, the coating is excessive, and the remaining urea, etc. may adhere to the device. It should be noted that, generally, the coating amount is per 1 m 2 However, in the present embodiment, since urea or the like is a reagent (reaction reagent) for reacting with cellulose fibers, it is preferably specified by the amount of urea per unit mass of cellulose fibers.

[0064] The pulp sheet having passed through the coating section 210 enters the post-drying section 220 to be dried.

[0065] In the drying of the post-drying section 220, for example, a hot air drying device, a gas heater drying device, an infrared drying device, or the like can be used. However, if an infrared drying device is used, urea or the like is solidified on the surface layer of the pulp sheet, which may hinder the penetration of urea or the like. Therefore, it is preferable to use a hot air drying device. In particular, the hot air drying device is easy to control the temperature, so if a multi-stage hot air drying device is provided and designed in a manner that the temperature is gradually increased, drying can be performed without hindering the penetration of urea or the like.

[0066] In the post-drying section 220, the drying temperature is preferably 80 to 140°C, more preferably 85 to 135°C, and particularly preferably 90 to 130°C. If the drying temperature is lower than 80°C, the drying may be insufficient when the drying time is short, so it is not suitable for high-speed production. On the other hand, if the drying temperature exceeds 140°C, by-products such as urea may be generated.

[0067] The moisture content of the pulp sheet after the post-drying section 220 is preferably 0 to 10%, more preferably 0 to 8%, and particularly preferably 0 to 7%. If the moisture content exceeds 10%, the reaction efficiency may decrease in the reaction section of the heating step described later.

[0068] In the post-drying section 220, the moisture content is a value measured by infrared light using a BM meter (basis weight / water content).

[0069] The surface temperature of the pulp sheet after passing through the post-drying section 220 is preferably 30 to 95° C., more preferably 35 to 90° C., and particularly preferably 40 to 85° C. If the surface temperature is lower than 40° C., drying may be insufficient. On the other hand, if the surface temperature exceeds 95° C., byproducts may be generated from the reaction reagents.

[0070] It should be noted that in this method, the production of paper itself is not the purpose, but the form of paper (pulp sheet) is only temporarily utilized, so the calendering step may be performed later, or the calendering step may be omitted and the reaction step may be performed.

[0071] (Heating step (urethanization step))

[0072] The pulp sheet (pulp fiber content) that has passed through the post-drying section 220 may be temporarily wound up in a winding section (not shown) and stored as a winding stock. Afterwards, the winding stock may be heated, cooled, or the like in a wound state to react urea or the like with the cellulose fibers, but in the present embodiment, the pulp sheet is pulled out from the winding stock and treated to be urethanized.

[0073] When the drawn pulp sheet is temporarily made into a winding material, it is preferred to dry it to a moisture content of 10% by mass or less, more preferably 9% by mass or less, and particularly preferably 8% by mass or less. This drying is performed to improve the reaction efficiency.

[0074] However, the manufacturing efficiency is reduced when the method of temporarily forming a coiled blank as described above is used. Therefore, the pulp sheet passing through the post-drying section 220 is preferably directly continuously entered (transferred) to the urethanization step X2. In this case, the above drying of the pulp sheet before urethanization can be omitted.

[0075] In the urethanization step X2, urea and the like contained in the pulp sheet, that is, the cellulose fiber-containing material, are reacted with the cellulose fibers. This reaction will be described in detail.

[0076] First, carbamate modification refers to modifying cellulose fibers into cellulose fibers having carbamate groups. In other words, it means that cellulose fibers are brought into a state where carbamate (ester of carbamic acid) is introduced.

[0077] The carbamate group is a group represented by -O-CO-NH-, for example, a group represented by -O-CO-NH2, -O-CONHR, -O-CO-NR2, etc. That is, the carbamate group can be represented by the following structural formula (1).

[0078] [Chemistry 1]

[0079]

[0080] Here, n represents an integer greater than 1. Each R is independently hydrogen, a saturated straight-chain hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated straight-chain hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, and at least one of derivatives thereof. In addition, cross-linked carbamate cellulose having a cross-linked structure formed between cellulose molecules or fibers by carbamate groups can be cited.

[0081] Examples of the saturated linear hydrocarbon group include linear alkyl groups having 1 to 10 carbon atoms, such as methyl, ethyl, and propyl groups.

[0082] Examples of the saturated branched hydrocarbon group include branched alkyl groups having 3 to 10 carbon atoms, such as isopropyl, sec-butyl, isobutyl and tert-butyl.

[0083] Examples of the saturated cyclic hydrocarbon group include cycloalkyl groups such as cyclopentyl, cyclohexyl and norbornyl.

[0084] Examples of the unsaturated straight-chain hydrocarbon group include straight-chain alkenyl groups having 2 to 10 carbon atoms such as vinyl, propen-1-yl and propen-3-yl, and straight-chain alkynyl groups having 2 to 10 carbon atoms such as ethynyl, propyn-1-yl and propyn-3-yl.

[0085] Examples of the unsaturated branched hydrocarbon group include branched alkenyl groups having 3 to 10 carbon atoms such as propen-2-yl, buten-2-yl and buten-3-yl, and branched alkynyl groups having 4 to 10 carbon atoms such as butyn-3-yl.

[0086] Examples of the aromatic group include a phenyl group, a tolyl group, a xylyl group, and a naphthyl group.

[0087] Examples of derivative groups include groups in which one or more hydrogen atoms possessed by the above-mentioned saturated straight-chain hydrocarbon groups, saturated branched hydrocarbon groups, saturated cyclic hydrocarbon groups, unsaturated straight-chain hydrocarbon groups, unsaturated branched hydrocarbon groups and aromatic groups are replaced by substituents (e.g., hydroxyl groups, carboxyl groups, halogen atoms, etc.).

[0088] In cellulose fibers having carbamate groups (carbamate introduced therein), part or all of the hydroxyl groups with high polarity are replaced by carbamate groups with relatively low polarity. Therefore, the hydrophilicity of the cellulose fibers is low, and the affinity with resins with low polarity is high. As a result, the fine fibers obtained by fibrillating the cellulose fibers have characteristics such as excellent uniform dispersibility with the resin. In addition, the slurry of the fine fibers has low viscosity and good handling properties.

[0089] The lower limit of the degree of substitution of the hydroxyl groups of the cellulose fiber by the carbamate groups is preferably 0.05, more preferably 0.1, and particularly preferably 0.2. If the degree of substitution is 0.05 or more, the effect of the introduction of the carbamate can be surely exerted. On the other hand, the upper limit of the degree of substitution is preferably 1, more preferably 0.5, and particularly preferably 0.4. In this regard, cellulose fibers with a high degree of substitution have the problem of being expensive.

[0090] It should be noted that cellulose is a polymer with anhydroglucose as a structural unit, and each structural unit has three hydroxyl groups. Therefore, if all hydroxyl groups are replaced by carbamate groups, the degree of substitution is 3.

[0091] The amount of carbamate groups introduced into the cellulose fibers is preferably 0.5 to 4.5 mmol / g, more preferably 0.6 to 4.0 mmol / g, and particularly preferably 0.7 to 3.5 mmol / g. If the substitution rate is less than 0.5 mmol / g, sufficient reinforcing effect may not be obtained when compounded with a resin. On the other hand, if the substitution rate exceeds 4.5 mmol / g, an excessive amount of urea may be required.

[0092] Regarding the introduction of carbamate into cellulose fibers (carbamate treatment), there are two methods: carbamate treatment of cellulose fibers followed by micronization, and a method of micronizing cellulose fibers to make microfibers followed by carbamate treatment. However, it is preferred to first perform carbamate treatment and then perform fiber opening as in the present embodiment. This is because the dehydration efficiency of cellulose fibers before fiber opening is high, and the cellulose fibers are easily opened by the heating accompanying carbamate treatment.

[0093] Conventionally, the process of carbamateizing cellulose fibers includes, for example, a mixing process, a removing process, a heating process, etc. In the mixing process, cellulose fibers and urea or the like are mixed in a dispersion medium. However, if this process is added, the production efficiency is significantly reduced. Therefore, in this method, urea or the like is reacted with cellulose fibers in the form of a strip-shaped pulp sheet. At this time, the pulp sheet can be considered to be in the form of a winding stock or in the form of a pulled-out pulp sheet, but in terms of excellent reaction efficiency and reaction uniformity, it is in the pulled-out state.

[0094] As urea and urea derivatives, for example, urea, thiourea, biuret, phenylurea, benzylurea, dimethylurea, diethylurea, tetramethylurea, compounds obtained by replacing the hydrogen atoms of urea with alkyl groups, etc. can be used. These ureas or urea derivatives can be used alone or in combination. Among them, urea is preferably used.

[0095] In the carbamate-forming step X2 of the present embodiment, a pulp sheet, i.e., a cellulose fiber-containing material P2 including urea or the like, is subjected to a heat treatment. In the carbamate-forming step X2, a part or all of the hydroxyl groups of the cellulose fibers react with urea or the like and are replaced with carbamate groups. More specifically, when urea or the like is heated, it is decomposed into isocyanic acid and ammonia as shown in the following reaction formula (1). Moreover, the reactivity of isocyanic acid is very high, and, for example, as shown in the following reaction formula (2), it forms carbamate with the hydroxyl groups of cellulose.

[0096] NH2-CO-NH2→HN=C=O+NH3…(1)

[0097] Cell-OH+HN=C=O→Cell-O-CO-NH2…(2)

[0098] As described above, the pulp sheet may be heated directly in a wound state or may be pulled out from a wound billet and heated. When the pulp sheet is heated directly in a wound state, a hot air heating method, a high frequency heating method, a rotary kiln method, etc. may be used as the heating device. On the other hand, when the pulp sheet is pulled out from a wound billet and heated, an induction heating roller, an oil heating roller, hot air heating, far infrared heating, microwave heating, etc. may be used as the heating device.

[0099] Here, the characteristics when the above heating device is used will be described.

[0100] First, the heating method is roughly divided into two types (intermittent type and continuous type (roll-to-roll type)). In the intermittent type, there are high-frequency heating devices and rotary kilns, which are equipment that can react a large number of samples at a time. In this regard, in the high-frequency heating device, when the object to be heated is placed in the electrode, polarization is caused inside the heated object to generate electric charge, and due to the speed change of the frequency, the molecules undergo intense internal friction and are heated. On the other hand, the rotary kiln is a rotating high-temperature firing device, and is used in the reagent recovery process of the kraft pulping process in the papermaking industry.

[0101] On the other hand, in the roll-to-roll type in which the pulp sheet is heated by passing it between a pair of rollers, in order to continuously heat the pulp sheet coated with urea, there are induction heating rollers, oil heating rollers, and hot air heating, far infrared heating, and microwave heating that can perform continuous heating. In this regard, the induction heating roller is a method of heating the roller itself by the action of an electrically generated magnetic field, and is also used in calendering equipment in the papermaking process. In addition, the oil heating roller is a method of heating the roller surface by circulating heated oil inside the roller. In addition, hot air heating is a method of spraying hot air from nozzles arranged above and below the conveyor belt to the upper and lower surfaces of the pulp sheet to heat the pulp sheet passing therebetween. In addition, far infrared heating is a method of radiating infrared rays with a wavelength of 3μm to 1mm and utilizing contraction and angular motion between atoms to perform heating. In addition, microwave heating is a method of generating heat by utilizing the phenomenon of frictional heat generated between molecules constituting the pulp sheet according to the frequency (300MHz to 30GHz), and microwave ovens are generally used.

[0102] Compared with oil-type heating rollers, reaction equipment using induction heating rollers is preferred because of their high reaction efficiency and energy efficiency. On the other hand, intermittent heating using the state of coiling the billet, especially heating using high frequency, causes uneven reaction because a large amount of sample is heated at one time, making it difficult to perform a uniform urethane reaction.

[0103] On the other hand, in continuous heating other than roll-to-roll heating such as induction heating rolls and oil heating rolls, or non-contact heating methods such as hot air heating and far infrared heating, the urethanization reaction can be advanced by increasing the reaction temperature.

[0104] As a conclusion, it can be said that it is particularly preferable to pass a strip-shaped pulp sheet containing urea or the like made by papermaking raw material pulp P1 between a pair of rolls and heat it, and to react by the heating. Among them, when the sheet width of the pulp sheet is 300 to 1000 mm, it is more preferable that at least one of the pair of rolls is a heating roll. In this case, for example, the heating temperature of the heating roll is preferably 180 to 280°C, more preferably 200 to 270°C, and particularly preferably 220 to 260°C.

[0105] Among them, first, the pulp sheet preferably passes between the rolls at a speed (line speed) of 300 to 3000 m / min, more preferably 400 to 2500 m / min, and particularly preferably 500 to 2000 m / min. If the line speed is less than 300 m / min, the production speed is slow and is not suitable for mass production. On the other hand, if the line speed exceeds 3000 m / min, the pulp sheet may break (paper break).

[0106] In addition, it is preferred that two or more pairs of rolls are provided in a row, and the first one or more pairs of rolls are used as a drying section, and the second one or more pairs of rolls are used as a reaction section. By allocating part of the heating process to the drying section instead of the reaction section, the reaction (modification), i.e., urethanization, proceeds sufficiently, and the physical properties of the pulp sheet flowing into the reaction section become uniform, so that the urethanization rate and the like also become uniform.

[0107] It should be noted that the pulp sheet can also be dried before the heating process. However, unlike the case where a portion of the pulp is allocated to the drying section instead of the reaction section for drying in the heating process, if the pulp sheet is dried before the heating process, it will be affected when moving in the process (device). In addition, in the case where a portion of the pulp is allocated to the drying section instead of the reaction section in the heating process, the inlet moisture content of the reaction section is 5% by mass or less. That is, the period when the moisture content exceeds 5% by mass is the drying section.

[0108] In the urethanization step X2 of the present embodiment, the temperature of the rollers belonging to the drying section (drying temperature) is preferably 80°C to 130°C, more preferably 90°C to 130°C, and particularly preferably 100°C to 130°C. If the drying temperature is lower than 80°C, the urethanization in the reaction section following the drying section may not be sufficiently performed. On the other hand, if the drying temperature exceeds 130°C, the water reacts with the urea and decomposes, and the urethanization may not be sufficiently performed. It should be noted that it is more preferable that the drying temperature of all the rollers belonging to the drying section is within the above range.

[0109] In the urethanization step X2 of the present embodiment, the temperature of the rollers belonging to the reaction section (reaction temperature) is preferably 220 to 280°C, more preferably 230 to 270°C, and particularly preferably 240 to 260°C. If the reaction temperature is lower than 220°C, sufficient reaction (urethanization) may not be possible. On the other hand, if the reaction temperature exceeds 280°C, urea and the like may be thermally decomposed, and coloring may become significant. It should be noted that it is more preferable that the reaction temperature of all rollers belonging to the reaction section is within the above range.

[0110] It should be noted that, when the heating step is not divided into a drying section and a reaction section as described above, when urea or the like is reacted with the cellulose fibers, the heating temperature in the urethanization step X2 is preferably 150 to 280° C., more preferably 160 to 270° C., and particularly preferably 180 to 260° C. If the heating temperature is lower than 150° C., sufficient reaction may not occur. On the other hand, if the heating temperature exceeds 280° C., urea or the like may be thermally decomposed, and coloring may become significant.

[0111] In this case (when the heating step is not divided into a drying section and a reaction section), the heating time in the urethanization step X2 is preferably 1 to 60 seconds, more preferably 1 to 30 seconds, and particularly preferably 1 to 20 seconds. If the heating time exceeds 60 seconds, coloring may become significant, and productivity may be poor.

[0112] In this case (when the heating process is not divided into a drying section and a reaction section), the point that the system is constructed in multiple stages (two or more pairs of rollers are provided) is the same, but it is preferred that the heating temperature of the first stage is suppressed to 80 to 140°C (more preferably 90 to 120°C), and the heating temperature of the second and subsequent stages is set to 180 to 280°C (more preferably 200 to 280°C). In addition, it is also possible to construct the system as follows: the heating temperature of each heating roller is set between 80 and 280°C, and the heating temperature is increased stepwise. In this case, instead of setting the first stage to a low temperature as described above, it is also preferred that the clamping line pressure of the pair of rollers of at least one stage is set to 1 to 100,000 N / cm, preferably 10 to 50,000 N / cm. It should be noted that according to the above structure, there is an advantage that the shrinkage of the pulp sheet can be suppressed.

[0113] The number of pairs of rollers belonging to the drying section and the number of pairs of rollers belonging to the reaction section may be one or more than two groups. However, it is preferred that the number of each group is set to a number of groups in which the passage time of the drying section is more than 8 seconds and the passage time of the reaction section is more than 8 seconds, more preferably a number of groups in which the passage time of the drying section is 8 to 30 seconds and the passage time of the reaction section is 8 to 30 seconds, and particularly preferably a number of groups in which the passage time of the drying section is 10 to 20 seconds and the passage time of the reaction section is 10 to 20 seconds. If the passage time is shortened (the number of pairs of rollers is reduced), carbamate formation may become insufficient. On the other hand, if the passage time is extended (the number of pairs of rollers is increased), carbamate formation may reach a limit in the case of the drying section, and carbamate formation may also reach a limit in the case of the reaction section, thereby degrading cellulose.

[0114] When the heating process is divided into a drying section and a reaction section as described above, the moisture content of the pulp sheet entering the drying section is preferably 15% or less, more preferably 10% or less, and particularly preferably 8% or less. If the moisture content exceeds 15%, the drying energy in the drying section may become enormous.

[0115] In this form, the said water content is the value measured by infrared rays using a BM meter (basis weight / water content).

[0116] When the heating process is divided into a drying section and a reaction section, the surface temperature of the pulp sheet entering the drying section is preferably 15 to 130° C., more preferably 20 to 100° C., and particularly preferably 25 to 70° C. If the surface temperature is lower than 15° C., additional heating energy may be required in the drying section. On the other hand, if the surface temperature exceeds 130° C., urea may decompose before the reaction.

[0117] When the heating step is divided into a drying section and a reaction section, it is preferred that the basis weight of the pulp sheet entering the drying section be 50 to 800 g / m 2 , more preferably 80 to 400 g / m 2 If the basis weight is less than 50g / m 2 On the other hand, if the basis weight exceeds 800 g / m 2 , the sheet becomes thicker, and the drying efficiency and reaction efficiency may be reduced.

[0118] The basis weight of the pulp sheet is a value measured in accordance with JIS P 8124.

[0119] (Fiber opening process)

[0120] In this embodiment, the urethanized cellulose fibers P3 obtained as described above are pulverized or the like as necessary, and then opened (refined) in the fiber opening step X3. Through the fiber opening, urethanized fine fibers P4 are obtained.

[0121] In addition, in this form, fine fiber means the cellulose fiber whose average fiber width is 0.01-19 micrometers. For example, fine fiber includes microfibril cellulose (microfibrillated cellulose) and cellulose nanofiber.

[0122] In addition, the reactive cellulose fibers P3 may be opened immediately after being crushed, but it is preferred that the sheet-like or crushed reactive cellulose fibers P3 be dissociated in water before opening, and then dehydrated using a dehydration device such as a valveless filter to clean the reactive cellulose fibers P3. In addition, when a valveless filter is used for dehydration, the mat-like reactive cellulose fibers P3 after dehydration are sprayed to make the cleaning more complete. By cleaning, unreacted reaction liquid, by-products of the reaction liquid, or water-soluble impurities can be removed.

[0123] In the present embodiment, microfiber cellulose refers to fibers whose average fiber diameter is thicker than that of cellulose nanofibers. Specifically, for example, it is 0.1 to 19 μm, preferably 0.2 to 10 μm. If the average fiber diameter of the microfiber cellulose is lower than (less than) 0.1 μm, there is no change compared to the cellulose nanofibers. For example, when mixed with a resin, the strength (especially the bending modulus) of the resin may not be fully improved. In addition, the fiber opening time becomes longer and a large amount of energy is required. In addition, the dehydration of the cellulose fiber slurry deteriorates. If the dehydration deteriorates, a large amount of energy is required for drying. If a large amount of energy is applied during drying, the cellulose fibers are thermally degraded and the strength may be reduced. On the other hand, if the average fiber diameter of the microfiber cellulose is higher than (exceeds) 19 μm, there is no change compared to the pulp, and the reinforcing effect of the resin may become insufficient.

[0124] The method for measuring the average fiber diameter of fine fibers (microfiber cellulose and cellulose nanofibers) is as follows.

[0125] First, 100 ml of an aqueous dispersion of fine fibers having a solid content concentration of 0.01 to 0.1% by mass is filtered with a Teflon (registered trademark) membrane filter, and the solvent is replaced once with 100 ml of ethanol and three times with 20 ml of tert-butanol. Then, freeze-drying is performed, and osmium coating is performed to prepare a sample. For this sample, observation based on an electron microscope SEM image is performed at any magnification of 3,000 to 30,000 times according to the width of the fibers constituting it. Specifically, two diagonal lines are drawn on the observed image, and three straight lines passing through the intersection of the diagonal lines are drawn arbitrarily. Then, the width of a total of 100 fibers intersecting with the three straight lines is visually measured. In addition, the median diameter of the measured value is taken as the average fiber diameter.

[0126] The urethane cellulose fibers P3 or their pulverized products may be subjected to a pretreatment, a bleaching treatment, etc. by a chemical method before fiber opening.

[0127] As pretreatment using chemical methods, for example, hydrolysis of polysaccharides using acid (acid treatment), hydrolysis of polysaccharides using enzymes (enzyme treatment), swelling of polysaccharides using alkali (alkali treatment), oxidation of polysaccharides using oxidants (oxidation treatment), reduction of polysaccharides using reducing agents (reduction treatment), etc. can be exemplified. Among them, as pretreatment using chemical methods, enzyme treatment is preferably performed, and one or more treatments selected from acid treatment, alkali treatment, and oxidation treatment are more preferably performed. Enzyme treatment is described in detail below.

[0128] As the enzyme used in the enzyme treatment, at least any one of a cellulase enzyme and a hemicellulase enzyme is preferably used, and the two are more preferably used together. If these enzymes are used, the fiber opening of the cellulose fiber becomes easier. It should be noted that the cellulase enzyme causes the decomposition of cellulose in the presence of water. In addition, the hemicellulase enzyme causes the decomposition of hemicellulose in the presence of water.

[0129] As cellulase enzymes, for example, enzymes produced by Trichoderma (filamentous fungi), Acremonium (filamentous fungi), Aspergillus (filamentous fungi), Phanerochaete (basidiomycete), Trametes (basidiomycete), Humicola (filamentous fungi), Bacillus (bacteria), Schizophyllum (basidiomycete), Streptomyces (bacteria), Pseudomonas (bacteria), etc. can be used. These cellulase enzymes can be purchased as reagents or commercial products. Examples of commercially available products include Cellulosin T2 (manufactured by HBI), Meicelase (manufactured by Meiji Seika Co., Ltd.), Novozyme 188 (manufactured by Novozyme), Multifect CX10L (manufactured by Genencor), and cellulase enzyme GC220 (manufactured by Genencor).

[0130] In addition, as a cellulase enzyme, any one of EG (endoglucanase) and CBH (cellobiohydrolase) can also be used. EG and CBH can be used alone or in combination. In addition, they can also be used in combination with a hemicellulase enzyme.

[0131] As the hemicellulase enzyme, for example, xylanase, which is an enzyme that decomposes xylan, mannase, which is an enzyme that decomposes mannan, arabanase, which is an enzyme that decomposes arabinan, etc. can be used. In addition, pectinase, which is an enzyme that decomposes pectin, can also be used.

[0132] Hemicellulose is a polysaccharide other than pectin that is located between the cellulose microfibrils of the plant cell wall. There are many types of hemicellulose, and they also differ depending on the type of wood and the interlaminar space of the cell wall. In the secondary wall of coniferous trees, glucomannan is the main component; in the secondary wall of broad-leaved trees, 4-O-methyl glucuronoxylan is the main component. Therefore, in the case of obtaining fine fibers from coniferous bleached kraft pulp (NBKP), it is preferred to use mannanase. In addition, in the case of obtaining fine fibers from broad-leaved bleached kraft pulp (LBKP), it is preferred to use xylanase.

[0133] The amount of enzyme added relative to cellulose fiber is determined, for example, according to the type of enzyme, the type of raw wood (conifer or broadleaf tree), the type of mechanical pulp, etc. Among them, the amount of enzyme added relative to cellulose fiber is preferably 0.1 to 3% by mass, more preferably 0.3 to 2.5% by mass, and particularly preferably 0.5 to 2% by mass. If the amount of enzyme added is less than 0.1% by mass, it is possible that the effect of the addition of the enzyme cannot be fully obtained. On the other hand, if the amount of enzyme added is higher than 3% by mass, cellulose is saccharified, and the yield of fine fibers is likely to decrease. In addition, there is also a problem that the effect improvement consistent with the increment of the addition cannot be confirmed.

[0134] When a cellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weakly acidic region (pH = 3.0 to 6.9) from the aspect of the reactivity of the enzyme reaction. On the other hand, when a hemicellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weakly alkaline region (pH = 7.1 to 10.0).

[0135] The temperature during the enzyme treatment is preferably 30 to 70° C., more preferably 35 to 65° C., and particularly preferably 40 to 60° C., when any of a cellulase enzyme and a hemicellulase enzyme is used as the enzyme. If the temperature during the enzyme treatment is 30° C. or higher, the enzyme activity is not easily reduced, and the treatment time can be prevented from being prolonged. On the other hand, when the temperature during the enzyme treatment is 70° C. or lower, the inactivation of the enzyme can be prevented.

[0136] The time of the enzyme treatment is determined by, for example, the type of enzyme, the temperature of the enzyme treatment, the pH during the enzyme treatment, etc. Among them, the general enzyme treatment time is 0.5 to 24 hours.

[0137] After the enzyme treatment, the enzyme is preferably inactivated. Examples of methods for inactivating the enzyme include a method of adding an alkaline aqueous solution (preferably pH 10 or higher, more preferably pH 11 or higher), and a method of adding hot water at 80 to 100°C.

[0138] Next, the method of the alkali treatment will be described.

[0139] When alkali treatment is performed before fibrillation, the hydroxyl groups of hemicellulose and cellulose contained in the cellulose fibers are partially dissociated and the molecules are anionized, thereby weakening the intramolecular and intermolecular hydrogen bonds, thereby promoting the dispersion of the cellulose fibers during fibrillation.

[0140] As the alkali used in the alkali treatment, for example, organic bases such as sodium hydroxide, lithium hydroxide, potassium hydroxide, aqueous ammonia solution, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, and benzyltrimethylammonium hydroxide can be used. Among them, sodium hydroxide is preferably used from the viewpoint of production cost.

[0141] When enzyme treatment, acid treatment, or oxidation treatment is performed before fiber opening, the water retention of fine fibers can be reduced, the crystallinity can be increased, and the homogeneity can be improved. In this regard, if the water retention of microfiber cellulose is low, it is easy to dehydrate, and the dehydration property of cellulose fiber slurry is improved.

[0142] When cellulose fibers are treated with enzymes, acids, or oxidation treatments, the amorphous regions of hemicellulose or cellulose in pulp are decomposed. As a result, the energy required for fiber opening can be reduced, and the uniformity and dispersibility of cellulose fibers can be improved. However, pretreatment reduces the aspect ratio of microfiber cellulose, so when used as a resin reinforcement material, it is preferable to avoid excessive pretreatment.

[0143] On the other hand, as bleaching treatment, peroxide bleaching, hypochlorite bleaching, chlorine dioxide bleaching, persulfate bleaching, Oxone (potassium monopersulfate complex salt) bleaching, multi-stage bleaching treatment combining these, and reduction bleaching using dithionite, sodium borohydride, etc. can be performed.

[0144] The fiber opening of cellulose fibers can be performed by beating the raw material pulp using a homogenizer such as a refiner, a high-pressure homogenizer, an opposing collision type homogenizer, a high-pressure homogenization device, a mortar friction machine such as a grinder or a mill, a single-screw kneading machine, a multi-screw kneading machine, a kneading refiner, a jet mill, etc. Among them, it is preferably performed using a refiner or a jet mill.

[0145] The average fiber length of microfiber cellulose (average value of the length of single fibers) is preferably 0.02 to 2.0 mm, more preferably 0.05 to 1.5 mm, and particularly preferably 0.1 to 1.0 mm. If the average fiber length is less than 0.02 mm, a three-dimensional network of fibers cannot be formed, and the reinforcing effect of the resin may be reduced. On the other hand, if the average fiber length is more than 2.0 mm, the length is no different from that of the raw material pulp, so the reinforcing effect may be insufficient.

[0146] The average fiber length of the microfiber cellulose can be arbitrarily adjusted by, for example, selecting, pretreating, and fibrillating the raw material pulp P1.

[0147] The ratio of microfiber cellulose having a fiber length of 0.2 mm or less (fineness ratio) is preferably 20% or more, more preferably 40% or more, and particularly preferably 60% or more. If the ratio is less than 20%, the reinforcing effect of the resin may not be sufficiently obtained. On the other hand, there is no upper limit to the ratio of microfiber cellulose having a fiber length of 0.2 mm or less, and all of them may be 0.2 mm or less.

[0148] The aspect ratio of the microfibril cellulose is preferably 2 to 15,000, more preferably 10 to 10,000. If the aspect ratio is less than 2, a three-dimensional network cannot be constructed, and thus the reinforcing effect may be insufficient. On the other hand, if the aspect ratio is higher than 15,000, the microfibril cellulose becomes more entangled with each other, and the dispersion in the resin may be insufficient.

[0149] The aspect ratio is the value obtained by dividing the average fiber length by the average fiber width. It is known that the larger the aspect ratio, the more sites where hooks are generated, and thus the greater the reinforcing effect, but on the other hand, the ductility of the resin decreases in proportion to the increase in hooks.

[0150] The fibrillation rate of microfibril cellulose is preferably 1.0% to 30.0%, more preferably 1.5% to 20.0%, and particularly preferably 2.0% to 15.0%. If the fibrillation rate is higher than 30.0%, the contact area with water becomes too large, so even if the fiber can be opened within the range of an average fiber width of 0.1 μm or more, it may be difficult to dehydrate. On the other hand, if the fibrillation rate is lower than 1.0%, there are few hydrogen bonds between the fibrils, and a strong three-dimensional network may not be formed.

[0151] The fiber length and fibrillation rate of the fiber were measured using a fiber analyzer "FS5" manufactured by Valmet. In particular, the fibrillation rate is the ratio of the projected portion of the small fiber to the projected portion of the entire fiber, i.e., the raised portion / the entire fiber including the raised fibers.

[0152] The crystallinity of microfiber cellulose is preferably 50% or more, more preferably 55% or more, and particularly preferably 60% or more. If the crystallinity is less than 50%, although the miscibility with pulp and cellulose nanofibers is improved, the strength of the fiber itself is reduced, and thus the strength of the resin may not be improved. On the other hand, the crystallinity of microfiber cellulose is preferably 95% or less, more preferably 90% or less, and particularly preferably 85% or less. If the crystallinity is higher than 95%, the proportion of strong hydrogen bonds in the molecule increases, the fiber itself becomes rigid, and the dispersibility deteriorates.

[0153] The crystallinity of microfibril cellulose can be arbitrarily adjusted by, for example, selecting, pre-treating, and refining the raw pulp P1.

[0154] The crystallinity is a value measured in accordance with JIS K 0131 (1996).

[0155] The viscosity of the microfibril cellulose is preferably 2 cps or more, more preferably 4 cps or more. If the pulp viscosity of the microfibril cellulose is lower than 2 cps, it may be difficult to suppress the aggregation of the microfibril cellulose.

[0156] The viscosity of microfiber cellulose is a value measured in accordance with TAPPI T230.

[0157] The freeness of microfibril cellulose is preferably 500 ml or less, more preferably 300 ml or less, and particularly preferably 100 ml or less. If the freeness of microfibril cellulose exceeds 500 ml, the average fiber diameter of microfibril cellulose exceeds 10 μm, and the strength improvement effect of the resin may not be sufficiently obtained.

[0158] The freeness is a value measured in accordance with JIS P8121-2 (2012).

[0159] The zeta potential of the microfibril cellulose is preferably -150 to 20 mV, more preferably -100 to 0 mV, and particularly preferably -80 to -10 mV. If the zeta potential is lower than -150 mV, the compatibility with the resin is significantly reduced, and the reinforcing effect may become insufficient. On the other hand, if the zeta potential is higher than 20 mV, the dispersion stability may be reduced.

[0160] The water retention of microfiber cellulose is preferably 80 to 400%, more preferably 90 to 350%, and particularly preferably 100 to 300%. If the water retention is less than 80%, there is no difference from the raw material pulp, so the reinforcing effect may be insufficient. On the other hand, if the water retention is higher than 400%, the dehydration property tends to be poor and aggregation is easily generated. In this regard, since the hydroxyl group of the fiber is substituted with a carbamate group, the water retention of microfiber cellulose can be further reduced, and the dehydration property and drying property can be improved.

[0161] The water retention of microfibril cellulose can be arbitrarily adjusted by, for example, selecting, pretreating, and fibrillating the raw material pulp P1.

[0162] The water retention of microfiber cellulose is a value measured in accordance with Japanese TAPPI No. 26 (2000).

[0163] Next, cellulose nanofibers will be described.

[0164] In the present embodiment, the cellulose nanofibers are fine fibers similar to the microfiber cellulose and have a unique effect on improving the strength of the resin.

[0165] First, cellulose nanofibers can be obtained by fibrillating (refining) urethanized cellulose fibers P3. As the raw material pulp P1, the same raw material pulp as microfiber cellulose can be used, and preferably the same raw material pulp as microfiber cellulose is used.

[0166] The raw material fibers of cellulose nanofibers can be pretreated and opened in the same manner as in the case of microfiber cellulose. However, the degree of opening is different, for example, it is necessary to open the fibers in such a way that the average fiber diameter is less than 0.1 μm. The following description will focus on the differences from the case of microfiber cellulose.

[0167] The average fiber diameter (average fiber width; average value of the diameter of a single fiber) of the cellulose nanofiber is preferably 4 to 100 nm, more preferably 10 to 80 nm. If the average fiber diameter of the cellulose nanofiber is less than 4 nm, the dehydration property may be deteriorated. In addition, in the method of mixing the cellulose nanofiber with the dispersant, the dispersant cannot fully cover (cannot fully entangle) the cellulose nanofiber, and the dispersibility may not be fully improved. On the other hand, if the average fiber diameter of the cellulose nanofiber is higher than 100 nm, it can no longer be called a cellulose nanofiber.

[0168] The average fiber diameter of the cellulose nanofibers can be adjusted by, for example, selecting the raw material pulp P1, pretreating it, opening it, and the like.

[0169] It should be noted that, unless otherwise specified, the methods for measuring the physical properties of cellulose nanofibers are the same as those for microfiber cellulose.

[0170] The average fiber length (single fiber length) of the cellulose nanofibers is preferably 0.1 to 1,000 μm, more preferably 0.5 to 500 μm. If the average fiber length of the cellulose nanofibers is less than 0.1 μm, a three-dimensional network of cellulose nanofibers cannot be constructed, and the reinforcing effect may be insufficient. On the other hand, if the average fiber length of the cellulose nanofibers is greater than 1,000 μm, the fibers are easily entangled with each other, and the dispersibility may not be sufficiently improved.

[0171] The average fiber length of the cellulose nanofibers can be adjusted by, for example, selecting, pretreating, and fibrillating the raw pulp P1.

[0172] The crystallinity of the cellulose nanofibers is preferably 95 to 50%, more preferably 90 to 60%. When the crystallinity of the cellulose nanofibers is within the above range, the strength of the resin can be reliably improved.

[0173] The crystallinity can be arbitrarily adjusted by, for example, selecting, pretreating, and fiberizing the raw pulp P1.

[0174] The pulp viscosity of the cellulose nanofibers is preferably 1.0 cps or more, more preferably 2.0 cps or more. The pulp viscosity is the viscosity of the solution after dissolving cellulose in a copper ethylenediamine solution. The greater the pulp viscosity, the greater the degree of polymerization of the cellulose. When the pulp viscosity is 1.0 cps or more, dehydration properties can be imparted to the slurry, and the decomposition of the cellulose nanofibers can be suppressed when kneading with the resin, and a sufficient reinforcing effect can be obtained.

[0175] The cellulose nanofibers obtained by fiber opening can be pre-dispersed in an aqueous medium to prepare a dispersion liquid before mixing with other cellulose fibers as needed. The aqueous medium is particularly preferably all water (aqueous dispersion liquid). However, the aqueous medium can also be partly other liquids that are compatible with water. As other liquids, for example, lower alcohols with a carbon number of 3 or less can be used.

[0176] The B-type viscosity of the cellulose nanofiber dispersion (concentration 1%) is preferably 10 to 2,000 cp, more preferably 30 to 1,500 cp. If the B-type viscosity of the dispersion is within the above range, mixing with other cellulose fibers becomes easy and the dehydration property of the cellulose fiber slurry is improved.

[0177] The B-type viscosity (solid content concentration 1%) of the dispersion is a value measured in accordance with "Methods for measuring viscosity of liquids" of JIS-Z8803 (2011). The B-type viscosity is the resistance torque when the dispersion is stirred, and a higher value means more energy is required for stirring.

[0178] The urethane-modified microfibers are dispersed in an aqueous medium as required to prepare a dispersion (slurry). The aqueous medium is preferably entirely water, but an aqueous medium in which a portion is other liquids compatible with water may also be used. As other liquids, lower alcohols having a carbon number of 3 or less may be used.

[0179] The solid content concentration of the slurry is preferably 0.1 to 10.0% by mass, more preferably 0.5 to 5.0% by mass. If the solid content concentration is less than 0.1% by mass, excessive energy may be required for dehydration and drying. On the other hand, if the solid content concentration is higher than 10.0% by mass, the fluidity of the slurry itself decreases, and the dispersant may not be uniformly mixed.

[0180] Example

[0181] Next, examples of the present invention will be described.

[0182] First, a predetermined sizing agent is added to the pulp slurry, and papermaking is performed in a wire section so as to achieve a predetermined Cobb sizing degree. Next, the pulp is supplied to a press section and a pre-drying section to produce a pulp sheet so as to achieve a predetermined basis weight. Next, a urea aqueous solution of a predetermined concentration is applied and impregnated into the pulp sheet in a coating section, and the pulp sheet is dried in a post-drying section to obtain a urea-coated sheet.

[0183] The obtained urea-coated sheet was reacted in a roll-to-roll reactor at a predetermined drying temperature, reaction time, and residence time to obtain a urethanized sheet. Next, the urethanized sheet was diluted with water to a solid content concentration of 5% using a disintegrator and disintegrated. The urethanized pulp aqueous dispersion obtained by the disintegration was repeatedly dehydrated and washed twice. The washed urethanized pulp was opened using a lapping machine to obtain a predetermined fineness value to obtain urethanized microfiber cellulose (fiber width 15 μm).

[0184] The carbamate group introduction rate (mmol / g) of each of the obtained urethanized microfiber celluloses was examined. The results are shown in Table 1. The moisture content of the sheet at the entrance of the drying section was 8% by mass, and the surface temperature was 20°C.

[0185] [Table 1]

[0186]

[0187] Next, another embodiment of the present invention will be described.

[0188] A sizing agent is added to the pulp slurry, and papermaking is performed in a wire section so as to achieve a predetermined Cobb sizing degree, and then the pulp sheet is produced in a press section and a pre-drying section so as to achieve a predetermined basis weight. Next, the reaction reagent solution is impregnated and coated on the pulp sheet in the coating section (the meaning of coating is as described above, and whether or not a coating layer is formed on the surface of the pulp sheet is not a problem), and the pulp sheet is dried in a post-drying section to obtain a pulp sheet (cellulose fiber-containing material) impregnated with the reaction reagent solution. The obtained pulp sheet is reacted in the reaction device described in Table 1 to obtain a pulp sheet (reacted cellulose fiber) in which cellulose fibers are modified.

[0189] Next, the modified pulp sheet was diluted with water to a solid content concentration of 5% using a disintegrator and disintegrated. The aqueous dispersion of the modified cellulose fibers obtained by disintegration was repeatedly dehydrated and washed twice. The washed modified cellulose fibers were opened based on the fineness to obtain modified fine fibers (microfiber cellulose). The results are shown in Table 2.

[0190] It should be noted that the reaction efficiency in the table was calculated by the following formula.

[0191] Reaction efficiency = A / B × 100 (%)

[0192] A: Molar amount of carbamate introduced into cellulose after reaction (mol)

[0193] B: Molar amount of urea added before reaction (mol)

[0194] [Table 2]

[0195]

[0196] From these results, it is understood that the reaction mode has a significant influence not only on energy consumption but also on urethanization.

[0197] Industrial Applicability

[0198] The present invention can be used as a method for producing urethanized cellulose fibers.

[0199] Description of Reference Numerals

[0200] 100 Papermaking process

[0201] 110 Network Department

[0202] 120 Pressing Section

[0203] 130 Pre-drying section

[0204] 200 Coating process

[0205] 210 Coating Department

[0206] 220 Post-drying section

[0207] P1 Raw pulp

[0208] P2 Cellulose fiber content

[0209] P3 urethane cellulose fiber

[0210] P4 urethane microfiber

[0211] X1 Papermaking and coating process

[0212] X2 Urethane Process

[0213] X3 Fiber opening process

Claims

1. A method for producing carbamate-modified cellulose fibers, characterized in that: When producing carbamate-modified cellulose fibers in which a part or all of the hydroxyl groups of the cellulose fibers are modified with carbamate groups, The modification is performed by heating a pulp sheet containing urea or a urea derivative, which is formed into a strip by papermaking a raw material pulp, and passing it between a pair of rolls.

2. The method for producing carbamate-modified cellulose fibers according to claim 1, wherein The pulp sheet has a sheet width of 300 mm to 10000 mm, and at least one of the pair of rolls is a heated roll.

3. A method for producing carbamate-modified cellulose fibers, characterized in that: When producing carbamate-modified cellulose fibers in which a part or all of the hydroxyl groups of the cellulose fibers are modified with carbamate groups, A pulp sheet containing at least one of urea and a urea derivative, which is made into a strip by making raw material pulp into paper, is passed between a pair of rolls at a speed of 300 m / min to 3000 m / min and heated, and the modification is performed by the heating. The pair of rollers is provided as two or more sets of continuous pair of rollers, The first group or two or more groups are used as the drying part, and the second group or two or more groups are used as the reaction part. The temperature of the rollers in the drying section is set to 80° C. to 130° C., and the temperature of the rollers in the reaction section is set to 220° C. or higher. The number of sets of the pair of rolls is set to a number such that the passage time of the drying section is 8 seconds or longer and the passage time of the reaction section is 8 seconds or longer.

4. The method for producing carbamate-modified cellulose fibers according to claim 1 or claim 3, wherein: The moisture content of the pulp sheet entering the drying section is set to 15% by mass or less.

5. The method for producing carbamate-modified cellulose fibers according to claim 1 or claim 3, wherein: The surface temperature of the pulp sheet entering the drying section is set to 15°C to 130°C.

6. The method for producing carbamate-modified cellulose fibers according to claim 1 or claim 3, wherein: As continuous processes within the machine, a papermaking step of making a raw material pulp into a strip-shaped pulp sheet, a coating step of coating urea or a urea derivative on the pulp sheet, and a modification step of modifying the urea or the urea derivative are sequentially introduced as continuous processes within the machine.

Citation Information

Patent Citations

  • Fine cellulose fiber, manufacturing method therefor, slurry, and composite

    JP2019001876A

  • Cellulose nanofiber having carboxyl group and anionic group other than carboxyl group, and method for producing the same

    JP2021075665A